Using Limestone to Improve Soil Fertility and Growth of Mango (Mangifera Indica L.). Issue 8 (28th April 2018) - Correia, Marcus André Ribeiro; Flores, Rilner Alves; de Mello Prado, Renato; Natale, Willian; Rozane, Danilo Eduardo; Vale, Diego Wyllyam do
ABSTRACT: Soil acidity is one of the most important factors limiting crop production. The objective of this work was to evaluate the effects of limestone application on the soil chemical properties, nutrition and yield of mango plants in an orchard under implementation. The design was randomized blocks, with five limestone doses (0; 2; 4; 6 and 8 t ha −1 ) and four replications. Soil chemical analyses were performed (at 12, 24, 36 and 48 months after the experiment implementation) in the layers 0–20; 20–40 and 40–60 cm deep. Nutrition status and yield were assessed during the first and second crop seasons. The highest fruit yield was associated with the application of 3.9 and 3.8 t ha −1 of limestone in the 2008/09 and 2009/10 seasons, respectively, that is, the dose recommended by the literature for raising base saturation to 80%, as a function of the fertility conditions of the soil initially obtained.